ANALISIS PENGARUH HARGA MINYAK DUNIA, NILAI TUKAR RUPIAH, INFLASI DAN SUKU BUNGA SBI TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) - Bin Raudha Hanoeboen (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2017)
The research was conducted with the aim to know and test the influence of world oil price, rupiah exchange rate, inflation and SBI interest rate to Composite Stock Price Index (IHSG). This study uses secondary data obtained from Indonesia Stock Exchange (IDX), Bank of Indonesia (BI) and Central Bureau of Statistics (BPS) from January 2011 to December 2014. In this study method of data analysis used is descriptive and satatistic analysis. The results showed that world oil prices have a negative effect on IHSG with coefficient value of 0.086. the variable of exchange rate have positive and significant effect to dependent variable of IHSG, Inflation variable has negative effect to IHSG with coefficient value equal to 0,073, and SBI variable has negative effect to IHSG with coefficient value 0, 084.